(untitled) (Journal of Parents and Teachers, 2026)
The author of the article highlights the importance of research in an educational institution, as it serves as an indicator of its dynamism and progress. These pages contain excerpts from the White Paper on Educational Reform, along with a range of topics that could serve as a starting point for research. The aim is to ensure that research becomes an increasingly integral part of educational institutions.